Evaluation of Eye Diseases in Cats and Dogs - Çakı, Sena; Durmuş, Ali Said (My University, 2025)
Eye diseases, which are common in cats and dogs, can generally occur due to infectious agents and trauma. The aim of this study was to evaluate eye diseases commonly observed in cats and dogs. The material of the study consisted of 107 cats and 92 dogs of different ages, breeds and genders with eye diseases. The breed, age, gender, anamnesis information, when the complaints started and how the disease occurred were determined and recorded. Photographs of abnormal formations detected in the cases whose eye examinations were performed were taken. Appropriate treatment methods were applied to sick animals and their follow-up continued until recovery was achieved. In this study, conjunctivitis (40.20%) was found to be the most common eye disease in cats and dogs. In addition, symblepharon (15.57%), blepharitis (12.56%), keratoconjunctivitis sicca (8.54%), corneal ulcer (7.54%), strabismus (4.52%), third eyelid gland prolapse (cherry eye) (3.02%), trichiasis (2.01%), keratitis (1.51%), entropion (1.01%), thelazia (1.01%), meibomitis (0.50%), cyst dermoid (0.50%) and eye diseases due to foreign bodies (1.51%) were also detected. The findings of this study revealed that with a well-taken anamnesis, a detailed examination, a correct diagnosis and treatment, diseases that develop in the eye, which is a sensitive organ, can be successfully treated.
Keywords: Dog; cat; Eye disease